2017
DOI: 10.1155/2017/1472642
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Wharton Jelly-Derived Adult Mesenchymal Stem Cells, in Biohybrid Scaffolds, for Experimental Skin Regeneration

Abstract: The ultimate goal for skin tissue engineering is to regenerate skin lesions to allow the full restoration of morphological and functional properties as what they were before injury. To this end, we have assembled a new prototype of a biomimetic human umbilical cord adult mesenchymal stem cell (hUCMS)/fibrin-based scaffold. We have fully characterized the proposed dermal equivalent (DE) in vitro, to assess morphological, functional, and biological properties of the encased cells. We transplanted DE subcutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The hUCMSCs migrated into the wound and decreased the quantity of inflammatory cells, while neovascularization was increased compared to the control groups . A biomimetic scaffold with hUCMSCs and fibrin showed an improved full‐thickness skin wound repair without scar formation in rats compared to controls without scaffold or with a scaffold without hUCMSC . Similarly, hUCMSCs in combination with a collagen‐fibrin double layer membrane and a single layer collagen membrane resulted in accelerated wound repair in mice when compared to mice treated without hUCMSC…”
Section: Umbilical Cord: From Waste Materials To Source Of Therapeuticmentioning
confidence: 99%
See 1 more Smart Citation
“…The hUCMSCs migrated into the wound and decreased the quantity of inflammatory cells, while neovascularization was increased compared to the control groups . A biomimetic scaffold with hUCMSCs and fibrin showed an improved full‐thickness skin wound repair without scar formation in rats compared to controls without scaffold or with a scaffold without hUCMSC . Similarly, hUCMSCs in combination with a collagen‐fibrin double layer membrane and a single layer collagen membrane resulted in accelerated wound repair in mice when compared to mice treated without hUCMSC…”
Section: Umbilical Cord: From Waste Materials To Source Of Therapeuticmentioning
confidence: 99%
“…147 A biomimetic scaffold with hUCMSCs and fibrin showed an improved full-thickness skin wound repair without scar formation in rats compared to controls without scaffold or with a scaffold without hUCMSC. 148 Similarly, hUCMSCs in F I G U R E 4 Following detection of a cleft lip and/or palate (CL/P) using prenatal ultrasound screening, cord blood stem cells are isolated upon birth. These stem cells express antifibrotic factors and anti-inflammatory factors and can be used in tissue engineering strategies in combination with factors targeting inflammation and fibrosis (e.g.…”
Section: Umbilical Cord: From Waste Materials To Source Of Therapeutmentioning
confidence: 99%
“…At preclinical level ( Table 1 ), since 2015, fourteen studies have analyzed the use of hMSCs for wound healing therapies in mouse or rat models. These cells have been isolated from different human tissues such as adipose tissue (hAT-MSCs) ( Li et al, 2016 ; Hersant et al, 2019 ; Xiao et al, 2019 ; Zomer et al, 2020 ), bone marrow (hBM-MSCs) ( He et al, 2019 ), umbilical cord blood (hUCB-MSCs) ( Montanucci et al, 2017 ; Yang et al, 2017 ; Xu et al, 2019 ; Myung et al, 2020 ; Zhang et al, 2020 ), Wharton’s Jelly (hWJ-MSCs) ( Ertl et al, 2018 ; Millán-Rivero et al, 2019 ), dermal papilla (hDP-MSCs) ( Zomer et al, 2020 ), placenta (hP-MSCs) ( Ertl et al, 2018 ), menstrual fluid (hMen-MSCs) ( Cuenca et al, 2018 ), amnion (hA-MSCs) ( Ertl et al, 2018 ), and jaw bone marrow (hJM-MSCs) ( He et al, 2019 ). In one study the human source of hMSCs was not indicated ( Chen et al, 2017 ).…”
Section: Mesenchymal Stem Cells In Cutaneous Injuries or Diseasesmentioning
confidence: 99%
“…Tissue engineering (TE) is another type of advanced therapy which has been investigated for the treatment of wounds and ulcers ( Table 1 ). From 2015, five studies have reported the use of hMSCs to evaluate their potential clinical benefits as tissue-engineered skin substitute (TESS) ( Chen et al, 2017 ; Montanucci et al, 2017 ; Yang et al, 2017 ; Ertl et al, 2018 ; Zomer et al, 2020 ). Mean time of follow-up for this strategy was 29.2 ± 20.4 days and the hMSCs populations analyzed were hUCB-MSCs ( Montanucci et al, 2017 ; Yang et al, 2017 ), hA-MSCs, hP-MSCs, hWJ-MSCs ( Ertl et al, 2018 ), hDP-MSCs, hAT-MSCs ( Zomer et al, 2020 ), and one where the source was not indicated ( Chen et al, 2017 ).…”
Section: Mesenchymal Stem Cells In Cutaneous Injuries or Diseasesmentioning
confidence: 99%
See 1 more Smart Citation